Advancements in Bioelectricity Generation Through Nanomaterial-Modified Anode Electrodes in Microbial Fuel Cells - Dessie, Yilkal; Tadesse, Sisay (Frontiers in Nanotechnology, 2022)
The use of nanotechnology in bioelectrochemical systems to recover bioelectricity and metals from waste appears to be a potentially appealing alternative to existing established procedures. This trend exactly characterizes the current renewable energy production technology. So, this review focuses on the improvement of the anode electrode by using different functional metal oxide-conducting polymer nanocomposites to enhance microbial fuel cell (MFC) performance. Enhancement of interfacial bioelectrocatalysis between electroactive microorganisms and hierarchical porous nanocomposite materials could enhance cost-effective bioanode materials with superior bioelectrocatalysis activity to MFC. In this review, efficiency improvement of MFC by using iron oxide and manganese oxide-based polypyrrole hybrid composites as model anode modifiers was discussed. The review also extended to discussing and covering the principles, components, power density, current density, and removal efficiencies in biofuel cell systems. Also, this research review demonstrates the applications of MFC for renewable energy generation, wastewater treatment, and metal recovery. This is due to having its own unique working principle at mild conditions and using renewable biodegradable organic matter as a direct fuel source.